Sulfur-modified tea-waste biochar improves rice growth in arsenic contaminated soil and reduces arsenic accumulation - Saurabh Kumar Pathak; Shraddha Singh; Vishnu D. Rajput; Shengdao Shan; Sudhakar Srivastava (iScience)
Summary: Arsenic (As) is a non-essential carcinogenic metalloid and an issue of concern for rice crops. This study investigated the effects of sulfur-loaded tea waste biochar (TWB) due to modification with sodium sulfide (SSTWB) or thiourea (TUTWB) on As stress and accumulation in rice plants. The results showed that sulfur-modified TWB improved plant morphology compared to plants grown in As-contaminated soil alone. Biochar amendments elevated the activity of antioxidant enzymes in rice plants harvested at 15 and 30 days after transplant (DAT). Additionally, SSTWB and TUTWB significantly reduced As content in shoots by 26% and 19% at 15 DAT, respectively, as compared to TWB. This trend continued at 30 DAT with SSTWB achieving the maximum decrease of 30%. Similar reductions were observed in plant roots. The study suggests that sulfur-modified biochar amendments offer a promising strategy to mitigate the negative effects of As on, and reduce its accumulation in, rice.